Whiskers in the dark [large type] - Brown, Rita Mae; Brown, Sneaky Pie, 1982- (Brown, Rita Mae. Mrs. Murphy mystery, 2019)
The discovery of a body in the beautiful Blue Ridge mountains dredges up mysteries that have lingered from Revolutionary Virginia through the Civil War and beyond, in a supernaturally thrilling new tale from Rita Mae Brown and her feline co-author Sneaky Pie Brown. A trial is underway in Albemarle County, where Mary Minor "Harry" Harristeen and her trusty crew of two- and four-legged friends hope to catch a killer--who may not be the person accused of the crime. Since an old friend's body was discovered by the hunting club's faithful beagles, it has been up to Harry--with her crime-solving cats Mrs. Murphy and Pewter, and Tee Tucker the corgi--to sniff out a trail of clues. Meanwhile, bloodshed dating back generations continues to haunt the current grounds of the National Beagle Club of America. Are past claims of ghost sightings still to be ignored? And what do these paranormal apparitions have to do with the very modern drama unfolding in court and the all-too-real threats confronting Harry and her companions at every turn?"--